THE URGENCY OF CIVIL LAW REFORM IN ACCOMMODATING THE DEVELOPMENT OF THE DIGITAL ECONOMY IN INDONESIA - Royhanah Qotrun Nada nada (JURNAL LAWNESIA (Jurnal Hukum Negara Indonesia), 2026)
The development of the digital economy in Indonesia has encouraged the emergence of various new forms of legal relationships conducted through electronic media, such as e-commerce transactions, electronic contracts, and the use of digital technology in business activities. This condition poses challenges to Indonesian civil law, which is fundamentally still based on the Indonesian Civil Code (Kitab Undang-Undang Hukum Perdata). This study aims to analyze the existing civil law regulations in accommodating the development of the digital economy in Indonesia and to examine the urgency and direction of civil law reform in order to provide legal certainty in the digital era. This research employs a normative legal research method using a statutory approach and a conceptual approach. The findings indicate that civil law regulations related to the digital economy are currently supported by the Indonesian Civil Code, the Electronic Information and Transactions Law, and various implementing regulations that recognize the validity of electronic contracts, electronic documents, and digital transactions. However, these regulations have not fully addressed technological developments, such as smart contracts, digital assets, and personal data protection. Therefore, civil law reform is necessary through the establishment of a more adaptive, responsive, and technology-oriented legal system to ensure legal certainty, legal protection, and justice for actors in the digital economy. Such reform is also expected to support the sustainable growth of Indonesia’s digital economy.